Evaluation of the Use of Digital Booklets on Increased Knowledge and Motivation of Pregnant Women in Exclusive Breastfeeding - Lia Nurlia Wiganda; Rahayu Khairiah (CV. Inara, 2024)
Background: The main focus of the Indonesian Ministry of Health is to reduce the stunting rate, the Maternal Mortality Rate (MMR) and the Infant Mortality Rate (IMR). Based on health profile data for 2019, there were 20,244 children aged 0-28 months who died, with the main cause of death being diarrhea. Exclusive breastfeeding has been shown to be effective in preventing stunting and reducing the risk of diarrhea. However, only 34% of babies at the Tirtamulya Health Center received breast milk, and far below the target of 48%. To increase awareness of the importance of breastfeeding, it is recommended to use a booklet containing information about the benefits of breastfeeding. The digital booklet is a version that can be accessed via mobile devices to make it easier to access information. Purpose of Writing: Describe the effect of digital booklets on the level of knowledge and motivation of third trimester pregnant women regarding exclusive breastfeeding at the Tirtamulya Health Center.Research Method : This study used a quasi-experimental design with pre-test and post-test with the control group. A total of 15 pregnant women in the third trimester were selected as samples for each group. Purposive sampling method was used for sampling. The independent variable in this study was the provision of digital booklets and videos, while the dependent variable was the level of knowledge and motivation about exclusive breastfeeding in third trimester pregnant women. Data collection is done through Google Form. Data analysis was performed using the Wilcoxon test and the Mann-Whitney test. Research results: Wilcoxon test of knowledge of the treatment group (p-value = 0.004), the control group (p-value = 0.008), the motivation of the treatment group (p-value = 0.002), the control group (p-value = 0.007). Mann Whitney test of knowledge (p-value = 0.017), motivation (p-value = 0.83). The treatment group had a mean value of knowledge and motivation that was greater than the control group. Conclusions and Suggestions: Digital booklets have a more significant effect on increasing the level of knowledge about exclusive breastfeeding among third trimester pregnant women compared to videos.